(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background. Obesity is defined as age- and sex-specific body mass index (BMI) at or above 95th percentile, it is one of the more pressing public health problems today. The common classification of weight is based on body mass index (BMI), calculated as the weight in kilograms divided by the square of the height in meters (kg/m2). We try to explain and limit the serious sequelae of this problem. Aim of study, determine the risk factors for obesity and its prevalence in childhood (5-15 years). Patients and Methods: Cross sectional study, from 1st of April 2017 to end of January 2018. Clusters of 1044 children aged 5 -15 years from primary and secondary schools, kindergarten and children admitted to the ward in Al-Diwaniya were surveyed, excluding endocrine diseases and those using medications like steroid. Data on age, gender, height and weight, to determine BMI, has been measured in this study. Results: The overall prevalence of obesity in the current study is 16.57 %, also we determined some of risk factors of obesity and we found that obesity has significant association with family history, residence and dietary habit of the child. Conclusion: The study determined the overall prevalence of obesity which is 16.57%, also we determined family history, residence and dietary habit as significant risk factor for obesity in childhood.